2011
DOI: 10.1089/ars.2010.3629
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Redox Imaging Demonstrates a Distinctive Response of Dopaminergic Neurons to Oxidative Insults

Abstract: Aims: The study of the intracellular oxido-reductive (redox) state is of extreme relevance to the dopamine (DA) neurons of the substantia nigra pars compacta. These cells possess a distinct physiology intrinsically associated with elevated reactive oxygen species production, and they selectively degenerate in Parkinson's disease under oxidative stress conditions. To test the hypothesis that these cells display a unique redox response to mild, physiologically relevant oxidative insults when compared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 62 publications
3
71
0
Order By: Relevance
“…To test this possibility, we used a probe for mitochondrial H 2 O 2 , MitoPY1, and found a robust rotenone-induced H 2 O 2 signal in VMB neurons but not cortical neurons. Whether this reflects differences in production or degradation of ROS remains to be determined, but these results are consistent with other recent work showing that VMB neurons handle ROS differently than cortical neurons (53). In fact, rotenone-exposed cortical neurons compared with vehicle showed less mtDNA damage both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…To test this possibility, we used a probe for mitochondrial H 2 O 2 , MitoPY1, and found a robust rotenone-induced H 2 O 2 signal in VMB neurons but not cortical neurons. Whether this reflects differences in production or degradation of ROS remains to be determined, but these results are consistent with other recent work showing that VMB neurons handle ROS differently than cortical neurons (53). In fact, rotenone-exposed cortical neurons compared with vehicle showed less mtDNA damage both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the decreased activity of TrxR in RTT cells compared to controls adds further understanding of how oxidative stress occurs in RTT. Overall, these data confirm the relevance of mechanisms controlling thiol/disulfide equilibria in the pathogenesis RTT and, in this respect, extend to neurodevelopmental disorders previous findings obtained in chronic neurodegenerative diseases [42,43]. It should be also mentioned that in previous work we have detected a decreased levels of GSH in RTT cells [44] and this can indirectly affect TrxR by maintaining Trx in the reduced state during oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this hypothesis, knockdown of endogenous α-synuclein in control rats ‘restored’ a TOM20:TOM22 PL signal in nigrostriatal neurons relative to the untransduced hemisphere (Figure 8A). Further, we have reported previously that, under basal conditions, nigrostriatal neurons exist in a more oxidized state than cortical or other dopaminergic neurons (31) – and results in figure 7 suggest that α-synuclein may contribute to this process. Here, in a separate cohort of animals, we found that AAV-sh[SNCA]-mediated knockdown of endogenous α-synuclein decreased basal levels of protein thiol oxidation in nigrostriatal neurons relative to the contralateral hemisphere, which received AAV-sh[control] (p<0.05; Figure 8B).…”
Section: Resultsmentioning
confidence: 62%